2022
DOI: 10.3748/wjg.v28.i29.3854
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitrergic neurons in colonic motility in a rat model of ulcerative colitis

Abstract: BACKGROUND The mechanisms underlying gastrointestinal (GI) dysmotility with ulcerative colitis (UC) have not been fully elucidated. The enteric nervous system (ENS) plays an essential role in the GI motility. As a vital neurotransmitter in the ENS, the gas neurotransmitter nitric oxide (NO) may impact the colonic motility. In this study, dextran sulfate sodium (DSS)-induced UC rat model was used for investigating the effects of NO by examining the effects of rate-limiting enzyme nitric oxide synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to reports, inflammatory mediators and their metabolites may alter neuromotor function, which would alter motility [ 3 , 22 , 42 , 59 ]. These inflammatory processes may also impact other organs in addition to the intestine [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to reports, inflammatory mediators and their metabolites may alter neuromotor function, which would alter motility [ 3 , 22 , 42 , 59 ]. These inflammatory processes may also impact other organs in addition to the intestine [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, some gastrointestinal motor dysfunctions have been attributed to alter NO generation or release [ 21 , 30 ]. Selective iNOS inhibition has been proposed as a therapy method for this potentially fatal illness, and it has been postulated that a toxic megacolon in individuals with ulcerative colitis may be generated by an excess of NO produced by iNOS in the colonic smooth muscles [ 45 ]. Colonic hypomotility seen in induced chronic pancreatitis has also been reported to be caused by elevated iNOS in the myenteric plexus, thus, proving the contribution of NOS in the pathogenesis of colonic dysmotility [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we predicted eight key active compounds in WDG that may be responsible for its therapeutic effects. Previous studies have reported that beta-sitosterol ( Kasirzadeh et al, 2021 ), stearic acid ( Sobocinska et al, 2022 ), linoleic acid ( Zhang et al, 2021 ), and lauric acid ( Li et al, 2022 ) exert pharmacological effects on the regulation of intestinal inflammation and the intestinal gut function, both of which are consistent with the mechanism of GMD. However, there remains a lack of reports on the effect of 4-tetradecenoic acid, 5Z-tetradecenoic acid, myristelaidic acid, and 11-dodecenoic acid on gastrointestinal disorders, prompting us to focus on these drugs with potential functions in GMD in future studies.…”
Section: Discussionmentioning
confidence: 62%